Redefining Nepal’s Foreign Policy on the Basis of Its Soft-Power Assets - K.C., Khadga; Timilsana, Binod Khanda (NCWA Annual Journal, 2023)
This paper examines the bilateral and multilateral relations of Nepal with soft power superpowers. It discusses the proper identification of soft power resources and instruments on their ground and mobilization of those to the targeted country using formal, public, and economic diplomacy with an aim of uplifting soft power ranks and indices. The homilies and diplomatic activities of Nepal have been examined using the soft power theory and the small state lens. In addition, it also aims to analyze Nepal's complex involvement in international affairs at the levels of governments, think tanks, research institutions, and academia. This paper has been prepared primarily based on desk research, mainly utilizing secondary data sources.